Publish or Paris - Megan MacDonald (Francosphères)
This article examines francophone publishing trends in Morocco and France, asking: what roles do the nation and languages play in transnational literary politics, and who reads francophone texts in Morocco and France? These questions are addressed through interviews with Moroccan writers and literary critics, a discussion of modes of literary production in Morocco and France, the role of Moroccan literature in the francophone sphere, the culture of ‘Death and Prizes’ in Morocco, and the politics of labelling Moroccan francophone literature ‘World Literature’. Ultimately, this article promotes close reading and a more literary treatment of Moroccan francophone literatures, rather than reinforcing the trend practised by some academics in the West who treat Moroccan francophone literature as a social lens through which to ‘read’ Morocco. Cet article est une réflexion sur les politiques d'édition entre France et Maroc. Quel est le rôle de la nation et celui du langage? Qui sont les lecteurs des textes francophones au Maroc et en France? Ces questions, soulevées par de nombreux écrivains et critiques littéraires lors d'entretiens que nous avons eus avec eux au Maroc, entrainent en outre des discussions sur les modes de production littéraire au Maroc et en France, sur la place de la littérature marocaine dans la sphère francophone, et le choix sémantique de parler de littérature monde à propos de la littérature marocaine. Finalement, je propose - non pas comme le font de nombreux universitaires de l'ouest de lire la littérature marocaine exclusivement comme espace sociale et ethnographique à travers lequel on peut ‘lire’ le Maroc - mais plutôt d'opérer une plongée dans la littérature / littérarité marocaine.